When Limb Surgery Has Become the Only Life-Saving Therapy in FOP: A Case Report and Systematic Review of the Literature - Botman, Esmée; Treurniet, Sanne; Lubbers, Wouter D.; Schwarte, Lothar A.; Schober, Patrick R.; Sabelis, Louise; Peters, Edgar J. G.; van Schie, Annelies; de Vries, Ralph; Grunwald, Zvi; Smilde, Bernard J.; Nieuwenhuijzen, Jakko A.; et al. (Frontiers in Endocrinology, 2020)
Fibrodysplasia ossificans progressiva (FOP) is a rare disease in which heterotopic ossification (HO) is formed in muscles, tendons and ligaments. Traumatic events, including surgery, are discouraged as this is known to trigger a flare-up with risk of subsequent HO. Anesthetic management for patients with FOP is challenging. Cervical spine fusion, ankylosis of the temporomandibular joints, thoracic insufficiency syndrome, restrictive chest wall disease, and sensitivity to oral trauma complicate airway management and anesthesia and pose life-threatening risks. We report a patient with FOP suffering from life-threatening antibiotic resistant bacterial infected ulcers of the right lower leg and foot. The anesthetic, surgical and postoperative challenges and considerations are discussed. In addition, the literature on limb surgeries of FOP patients is systemically reviewed. The 44 year-old female patient was scheduled for a through-knee amputation. Airway and pulmonary evaluation elicited severe abnormalities, rendering standard general anesthesia a rather complication-prone approach in this patient. Thus, regional anesthesia, supplemented with intravenous analgosedation and N2O-inhalation were performed in this case. The surgery itself was securely planned to avoid any unnecessary tissue damage. Postoperatively the patient was closely monitored for FOP activity by ultrasound and [18F]PET/CT-scan. One year after surgery, a non-significant amount of HO had formed at the operated site. The systematic review revealed seventeen articles in which thirty-two limb surgeries in FOP patients were described. HO reoccurrence was described in 90% of the cases. Clinical improvement due to improved mobility of the operated joint was noted in 16% of the cases. It should be noted, though, that follow-up time was limited and no or inadequate imaging modalities were used to follow-up in the majority of these cases. To conclude, if medically urgent, limb surgery in FOP is possible even when general anesthesia is not preferred. The procedure should be well planned, alternative techniques or procedures should be tested prior to surgery and special attention should be paid to the correct positioning of the patient. According to the literature recurrent HO should be expected after surgery of a limb, even though it was limited in the case described.